A Comparative Study of Job Satisfaction In Public and Private Sector: Exploring Job Satisfaction in Public and Private Sectors: A Comparative Study (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Job satisfaction is a set of favorable or unfavorablefeelings with which employees view their work. It is a worker's sense ofachievement and success andis generally perceived to be directly linked toproductivity as well as to personal wellbeing. The happier people are withintheir job, the more satisfied theyare said to be. Job satisfaction impliesdoing a job one enjoys, doing it well, and being suitably rewarded for one'sefforts. Job satisfaction can beinfluenced by a variety of factors, e.g., thequality of one's relationship with their supervisor, the quality of thephysical environment in which they work,degree of fulfillment in their work,etc.. Job satisfaction further implies enthusiasm and happiness with one's workJob satisfaction; describes how satisfiedan individual is with his or her job.Job satisfaction is not the same as motivation, although it is closely linked,but satisfaction includes the managementstyle and culture, employeeinvolvement, empowerment and autonomous work groups. Job satisfaction is a veryimportant attribute which is frequently measured by organizations. The mostcommon way of measurement is the use of rating scales where employees reporttheir reactions to their jobs.Questions related to rate of pay, workresponsibilities, variety of tasks, promotional opportunities the work itselfand co-workers. For the organization, job satisfaction of its workers means awork force that is motivated and committed to high quality performance.Increased productivity—the quantity andquality of output per hour worked—seemsto be a byproduct of job satisfaction. Employee satisfaction surveys providethe information needed to improvelevels of productivity, job satisfaction, andloyalty. Organizations can identify the root causes of job issues and createsolutions for improvements with anaccurate perspective of employee viewsdiscover what motivates people, what drives loyalty, and what genuinely makesand keeps your employeeshappy. Satisfaction levels increase when an employeeknows that their issues are being addressed. There is a direct link betweenemployee jobsatisfaction and financial results. The more satisfied youremployees are the more motivated and committed they will be to yourorganization’s success.In this Research paper we have tried to make acomparison of Job satisfaction between Private and Govt. sector and tried tofind out the basic reasons ofdissatisfaction in job.